Phytochemical analysis and antimicrobial potential of Bauhinia tomentosa leaf extracts - Suyambumani, Subana; Pandiyan, Jeevan; Wong, Ling Shing; Djearamane, Sinouvassane; Mathanmohun, Maghimaa; Sagadevan, Suresh (Journal of Phytology, 2024)
Herbal medications have high demand in both advanced and budding nations because of their increased bioavailability and minimal side effects. In the present study, the ethanolic and acetone extracts from Bauhinia tomentosa leaf were investigated for their antibacterial potential against Gram-positive (Staphylococcus aureus), Gram-negative bacteria (Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa) and yeast (Candida albicans). Phytochemical examination revealed the presence of diverse secondary metabolites, such as flavonoids, alkaloids, phenolic compounds, tannins, and saponins in leaf extracts. GC-MS analysis detected 15 chemical constituents in the extracts, with the major compounds such as 2-Phenyl-1-3- Oxazol, Caryophyllne, dodecanoic acid, d-glycero-d-galacto-haptose, Phytol, Tetradecanoic acid, 1-Hexacosanol, Isophytol, Oleic acid, 7H-Purine-2-amine,7-methyl, and eicosane. Antibiotics study have been used to explore drug resistance in pathogens. These extracts exhibited concentration-dependent antibacterial activity against the tested bacterial strains. The acetone displayed higher antibacterial activity than the ethanol extract, which could be attributed to the efficiency of the solvent extract in extracting the bioactive compounds. The findings of this study offer valuable information regarding the phytochemical composition and antibacterial potential of B. tomentosa leaf extract. The bioactive compounds identified through GC-MS analysis may be responsible for the observed antibacterial activity. Furthermore, the leaf extracts were non-toxic, and their potent antibacterial effects may be attributed to the presence of bioactive phytoconstituents. Future studies may contribute to the development of B. tomentosa based antimicrobial agents with potential therapeutic applications.